Preschool and Primary Education - Mikk, Jaan; Veisson, Marika; Luik, Piret (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2011)
The studies in this volume explore a number of issues in education today. One paper reveals what actually motivates teachers to develop their career, another, how to teach primary teachers to talk about visual art. Children's artworks were explored in one article to see how they relate to their adjustment to school. In another, a case study was successful in developing reasoning in primary school students. The measurement of mathematics achievement revealed no difference between Estonian speaking and Russian speaking schools. Performance-related goals were shown in another article to be associated with the self-concept of the students. The learning disabilities of children were analysed, and the production of narratives by children with language impairment. The analysis of aggressive behaviour in children in Estonia and Finland indicated gender and country differences in their behaviour- Resumé vydavatel